Contribution to the flora of the Maltese Islands: Euphorbia subg. Chamaesyce and Euphorbia exigua s. l. (Euphorbiaceae) - Mifsud, Stephen (Phytotaxa, 2018)
The identity and the taxonomic treatment of the species belonging to Euphorbia subg. Chamaesyce occurring on the Maltese Islands were not adequately studied both in historical and recent literature. Apart from the native sand dune species Euphorbia peplis, all records have been previously attributed to the cosmopolitan weedy species E. maculata and E. chamaesyce. This work provides the first taxonomic synopsis based on the examination of 53 specimens collected from Malta and Gozo between 2014 and 2017. The study ascertained the occurrence of six species, of which E. serpens, E. prostrata and E. hypericifolia are first reported from the Maltese Islands. Discussion on the taxonomy, origin, ecology and invasiveness of these species is provided, together with photos and an identification key. Moreover, taxonomic studies on E. exigua s. l., belonging to subg. Esula, sect. Exiguae, have been carried out on Maltese material and discussed. E. exigua var. pycnophylla, originally described as endemic of the Maltese Archipelago and recorded afterwards on the Sicilian island of Lampedusa, bears no significant morphological trait which allows to clearly distinguish it from the nominal variety. No differences in fruit and seed morphology resulted when the two varieties were compared and the slight differences present in the habit of the plant and the arrangement of leaves has been judged to be of ecotypic origin, hence justifying the lumping of this variety into the single and variable taxon E. exigua.